Smart antennas. - Chryssomallis, Michael (IEEE Antennas & propagation magazine.)
Smart antennas have received increasing interest for improving the performance of wireless radio systems. These systems of antennas include a large number of techniques that attempt to enhance the received signal, suppress all interfering signals, and increase capacity, in general. The main purpose of this article is to provide an overview of the current state of research in the area of smart antennas, and to describe how they can be used in wireless systems. Thus, this article provides a basic model for determining the angle of arrival for incoming signals, the appropriate antenna beamforming, and the adaptive algorithms that are currently used for array processing. Moreover, it is shown how smart antennas, with spatial processing, can provide substantial additional improvement when used with TDMA and CDMA digital-communication systems. The material presented is tutorial in nature, leaving the details for further study from the papers appearing in the reference list.